Primary Hepatic Lymphoma Mimicking a Hepatocellular Carcinoma in a Cirrhotic Patient: Case Report and Systematic Review of the Literature - Ali Bohlok; Thierry De Grez; Fikri Bouazza; Roland De Wind; Melody El-Khoury; Deborah Repullo; Vincent Donckier (Case Reports in Surgery)
Introduction. Primary hepatic lymphomas (PHLs) are rare liver tumors, frequently misdiagnosed preoperatively. As these tumors could be successfully treated with chemotherapy, their early recognition is essential, potentially, to avoid useless surgery. We report on the case of a cirrhotic patient with hemochromatosis who presented a PHL, initially diagnosed as a hepatocellular carcinoma (HCC), and we analyze recent data from the literature on this subject. Case Presentation and Review of the Literature. A 45 mm liver tumor was found is a 68-year-old man with alcohol cirrhosis and hemochromatosis. At imaging, the diagnosis of HCC was suspected according to vascular characteristics and the presence of cirrhosis. FDG PET scan showed a solitary hypermetabolic liver tumor. Tumor markers were negative. Surgery consisted in left lateral hepatectomy. At pathology, the diagnosis of the primary hepatic marginal zone B cell lymphoma of mucosa-associated lymphoid tissue (MALT) type was demonstrated. Twenty-two articles reporting 33 cases of true PHL of MALT type were found. Presentation lacked specific symptoms (70% asymptomatic). Half of patients were suspected to have other etiologies of liver mass (HCC, intrahepatic cholangiocarcinoma), and thus diagnosis was established postoperatively. In the patient, diagnosis was made by preoperative biopsy, and chemotherapy was first-line treatment. Discussion. Preoperative diagnosis of PHL, and particularly of primary hepatic MALT lymphoma, is challenging. This case illustrates that PHL remains to be considered among the differential diagnosis of isolated solid liver tumors. Further, it indicates that biopsy could be still indicated in case of suspected HCC in cirrhotic patients, particularly in the presence of unusual findings such as the combination of a FDG PET scan positive tumor in the absence of elevated alpha-fetoprotein.